Pengaruh Dividen Change Dan Profitabilitas Terhadap Return Masa Depan Dengan kategori Saham Sebagai Variabel Moderasi (Survey Pada Kelompok Agribisnis/Non Agribisnis di Bursa Efek Indonesia Periode 2016-2020) - Anton Robiansyah; Edward Zubir; Sri Sukatmi (UNIVED Press, 2022)
ABSTRACT Investment, either directly or indirectly, aims to obtain certain benefits (profits) from the investment, with the hope of getting profits in the future. For a rational prospective investor, his attention will be directed to the rate of return on investment, and the chosen investment is the one that promises the highest return with a particular risk. Investors in investing must assess the risk of future returns through the influence of dividend changes and profitability in terms of the company's stock category. This study aims to determine the effect of dividend change and profitability on future returns, with the category of agribusiness/non-agribusiness companies being the moderating variable. The sample in this study consisted of 127 Agribusiness/Non-Agribusiness Group companies on the Indonesia Stock Exchange from 2016-to 2020 with the purposive sampling method. This research is quantitative research where the analytical tool used is a multiple linear regression test with SPSS version 22. The study's results indicate that the dividend change variable does not affect stock returns. At the same time, the level of profitability has a positive effect on stock returns. The classification of agribusiness companies does not moderate the effect of dividend changes and profitability on future returns. Key Words: Deviden Change, Profitabilitas, Return, and the company's stock category